2020
DOI: 10.32598/rj.21.1.3059.1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Perceptual-Motor Program Based on Johnstone and Ramon Method on Gross Motor Skills of Children With Visual Impairment: A Randomized Controlled Trial

Abstract: Objective The integration of various senses with each other in the form of perceptual-motor activities can lead to the promotion of different aspects of physical, perceptual, cognitive, and psychosocial development. Decreased visual acuity in children with visual impairment makes it difficult to develop motor skills, including gross motor skills. A few studies have used perceptual-motor interventions in these children with no specific framework. The purpose of this study is to evaluate the effect of a perceptu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
3
1
Order By: Relevance
“…In this study, martial arts instruction did not significantly promote aiming and catching, which was contrary to a previous structured physical activity intervention showing aiming and catching improvements in non-normally sighted children [ 53 ]. These inconsistencies may be related to the intervention contents, as the abovementioned study directly applied to aim and catching activities, which may be more likely to develop relevant motor skills through targeted reinforcement training.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In this study, martial arts instruction did not significantly promote aiming and catching, which was contrary to a previous structured physical activity intervention showing aiming and catching improvements in non-normally sighted children [ 53 ]. These inconsistencies may be related to the intervention contents, as the abovementioned study directly applied to aim and catching activities, which may be more likely to develop relevant motor skills through targeted reinforcement training.…”
Section: Discussioncontrasting
confidence: 99%
“…Secondly, multimodal sensory stimulation can strengthen the function of sensory integration and is more conducive to the development of motor ability [ 53 ]. In sensory–motor integration, sensory input signals are integrated by the central nervous system to assist in the execution of motor programs.…”
Section: Discussionmentioning
confidence: 99%
“…En 2017, la OMS anunció que la segunda y tercera categoría son consideradas como baja visión declarada con una agudeza visual inferior a 6.18. 31 Para que el desarrollo de un niño sano sea normal y óptimo, por algunos autores llamado también «jalones de desarrollo», en los que Silva, Moura y Nunes han concluido que éste debe seguir fases divididas en: eta-pa sensoriomotriz (cero a dos años), en la que el niño busca el desarrollo conjunto del esquema de acción sobre un objeto, ya que esto le permite construir el conocimiento físico de la realidad. Etapa preoperatoria (dos a seis años), dentro de ésta, el niño es capaz de construir una relación de causa y efecto, también es la fase de los «por qué» y toman a la figura paterna para resolver estas interrogantes.…”
Section: Resultsunclassified
“…In 2021, Rashidipour et al [23] assessed balance in children with visual disorder, and their results showed that protocols, like gaming, can improve balance in these children. Also, Mirzaie et al [24] showed that an intervention program of motion-perception can promote gross mobility skills in children with visual impairment. Cappagli [25] in 2019 showed that auditory-motor training can stop growth delay in children with low vision In 2019, Scally et al [26] figured out that growth of mobility skills, social interactions, and self-esteem in children with visual impairment can be increased.…”
Section: Discussionmentioning
confidence: 99%